Unilateral Biportal Endoscopic Discectomy: Technical Note - Bishokarma, Suresh; Yogi, Nikunja (Nepal Journal of Neuroscience, 2025)
Lumbar radiculopathy is a common clinical pathology with a lifetime incidence ranging from 13% to 40% and is associated with significant morbidity and socioeconomic burden. In cases where conservative therapy fails, discectomy is the standard surgical care for prolapsed intervertebral disc. There are various methods to remove the disc materials viz open discectomy, microscopic discectomy, transforaminal endoscopic discectomy, Percutaneous Endoscopic Lumbar Discectomy (PLED) or Unilateral biportal endoscopic discectomy (UBED). Surgical techniques of most of these methods are abundant in literature. However, there are few technical details on UBE. In this paper, we outline key technical steps to guide surgeons in performing UBE effectively. The technique described here represents one possible method among many, rather than a definitive protocol.